-2(14q-20)-4=-4(7q-9)

Simple and best practice solution for -2(14q-20)-4=-4(7q-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(14q-20)-4=-4(7q-9) equation:


Simplifying
-2(14q + -20) + -4 = -4(7q + -9)

Reorder the terms:
-2(-20 + 14q) + -4 = -4(7q + -9)
(-20 * -2 + 14q * -2) + -4 = -4(7q + -9)
(40 + -28q) + -4 = -4(7q + -9)

Reorder the terms:
40 + -4 + -28q = -4(7q + -9)

Combine like terms: 40 + -4 = 36
36 + -28q = -4(7q + -9)

Reorder the terms:
36 + -28q = -4(-9 + 7q)
36 + -28q = (-9 * -4 + 7q * -4)
36 + -28q = (36 + -28q)

Add '-36' to each side of the equation.
36 + -36 + -28q = 36 + -36 + -28q

Combine like terms: 36 + -36 = 0
0 + -28q = 36 + -36 + -28q
-28q = 36 + -36 + -28q

Combine like terms: 36 + -36 = 0
-28q = 0 + -28q
-28q = -28q

Add '28q' to each side of the equation.
-28q + 28q = -28q + 28q

Combine like terms: -28q + 28q = 0
0 = -28q + 28q

Combine like terms: -28q + 28q = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 0.8-z=2.1 | | 15x-2-6x=45 | | (2x-3)+(7x+21)=90 | | 13x-29=155 | | -9.39-3.4d=-1.1d | | x^2-3xy+3y^2+6y=7 | | 4x+4z-2y=-1 | | 7(X-6)= | | b-7=12# | | (3X)9=24 | | (3X)9=25 | | 0=-3x^2+4x | | X+2015=Y | | 4m+5=48 | | (2x-3)=90 | | P-25=-53 | | 6x+7x-5x=-48 | | 6y=5y-8.6 | | (2x-3)=180 | | x^3+(2-i)x^2+(-4-3i)x+(1+i)=0 | | 6g=18# | | -2(y+1)=-4y+10 | | [2x-1]=3x | | 36=(x-1)2+(y-5)2 | | 7y-c=b | | -7=2(w-6)-7w | | x^2-2k(1+3k)+7(3+2k)=0 | | n+(n-8)=n+15 | | 3x-a=c | | 3.5-x=9 | | x+4y=59 | | D(y)y=2x-7 |

Equations solver categories